Talent identification and development in Olympic triathlon: a perspective from Brazilian coaches - Vieira, L. A.; Werneck, F. Z.; Coelho, E. F.; Miranda, L.; de Lima, J. R. P. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2024)
The knowledge of coaches has been used in research on talent identification and development. The objective was to investigate how Brazilian triathlon coaches identify talents and what is the importance of different factors and indicators for the development of young triathletes. 37 coaches (89% male; 36.2 ± 8.3 years; 43% international competitive level) answered an online questionnaire about anthropometric, physical-motor, technical, tactical, psychological and environmental characteristics. On a scale of 1 (not very important) to 5 (extremely important), coaches indicated to what extent a factor/indicator of sporting potential was important for talent development in triathlon. 45.9% of the coaches perform talent identification, mainly by physical-motor tests and triathlon simulations. In talent development, the physical-motor factor was the most important, followed by the technical, psychological and anthropometric factor, and finally the tactical and environmental factor. Most coaches considered as extremely important the following indicators: determination (70%), aerobic endurance (65%), specific swimming skills (62%), ability to withstand pressure (59%), and efficiency of the cyclic gesture of swimming, cycling, and running (57%). We conclude that Brazilian triathlon coaches identify talents mainly through batteries of tests and triathlon simulations and consider the physical-motor factor the most important for the development of young talented triathletes, but not the only one.